Structural Change in Ethiopia : An Employment Perspective - Martins, Pedro (World Bank, Washington, DC, 2014)
This paper investigates whether the Ethiopian economy is undergoing a virtuous process of structural change. In particular, it assesses the relative contributions of within-sector and between-sector productivity to output per capita growth. Based on data disaggregated into eight sectors for the period 1996-2011, the analysis suggests that the structure of output has changed considerably -- predominantly from agriculture to services -- but changes in the composition of employment have lagged behind. Labor productivity growth has been strong across most sectors, albeit mainly driven by within-sector productivity improvements. Nonetheless, the pace of structural change is accelerating and its relative contribution to output growth is increasing.